An Analysis of Feminism Idea that represented by Queen Elizabeth I in the Shekhar Kapur's Film Entitled 'Elizabeth: The Golden Age' - Manda Handika; Sri Hartiningsih (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2014)
An Analysis of Feminism Idea that represented by Queen Elizabeth I in the Shekhar Kapur's Film Entitled 'Elizabeth: The Golden Age'